Pengujian Marshall dan Draindown Campuran SMA Kasar Menggunakan Agregat Gunung Bittuang - Reny (Universitas Kristen Indonesia Paulus, 2026)
SMA mixtures tend to experience flow where the asphalt separates from the aggregate at high temperature conditions. Draindown is carried out to understand the conditions in which the aggregate and asphalt separate from the mixture, so that the asphalt flows to the bottom of the mixture. The aim of this research was to determine the characteristics of Mount Bittuang stone in the Rough SMA mixture, then carry out the Draindown test to determine asphalt flow, the Marshall test to obtain the characteristics of the mixture and the Marshall Immersion test to obtain residual Marshall stability. The Draindown testing method uses SNI 8129-2015 and Marshall testing, namely SNI 06-2489-2018. From the test results of the Rough SMA mixture using Mount Bittuang stone for the Draindown test results, namely no more than 0.3%, from the Marshall test which was carried out with asphalt content of 6.00% - 7.00% for stability, flow, VIM, VMA and VFB values ​​that met specifications. The Optimum Asphalt Content is 6.50% with a coarse aggregate composition of 70.44%, fine aggregate 13.69%, filler 9.37% and asphalt 6.50%. Marshall Immersion test results obtained a value of 93.44%.